Mosby's comprehensive review of nursing for the NCLEX-RN examination - Nugent, Patricia M.; Green, Judith S.; Saul, Mary Ann Hellmer; Pelikan, Phyllis K. (St. Louis, Missouri : Elsevier, Mosby, 2012)
This is a resource that has helped nurses pass the NCLEX exam for over 60 years, the 20th edition is fully updated to reflect the newest NCLEX-RN test plan. Content review is presented in a concise and full-color outline format organized by the core areas of medical-surgical, pediatric, maternity/women's health, and mental health nursing, with a practice test following each unit. More than 4,200 practice questions and rationales, including more than 600 questions in the newest alternate item formats, are written by a team of trusted NCLEX experts led by the author. Key features include: Over 4,200 practice questions in the book and on the companion CD provide ample practice opportunities in both print and electronic testing formats. Review questions are grouped by categories of concern to focus study on any areas of weakness. Detailed rationales for correct and incorrect answers are provided with every question. Text references are provided with the answer rationales for further study of difficult topics. Two comprehensive exams are coded by clinical area, client need, nursing process, and cognitive level, to help evaluate strengths and weaknesses. An overview of the latest NCLEX-RN test plan describes the recent changes and additions to content. A companion CD allows the creation of customized quizzes and exams based on clinical area, NCLEX client needs category, nursing process, and cognitive level. New to this edition: Updated content reflects the newest NCLEX-RN test plan. 15% of total questions are alternate item formats, including new audio and graphic option formats. An NCLEX Preparation Toolkit and two comprehensive exams help to strategize review across clinical disciplines. Hundreds of new or revised questions reflect the increased emphasis on management of care, patient safety, and alternate format items. A new section on nursing management discusses key concepts such as delegation and leadership. Downloadable audio summaries for medical-surgical nursing topics allow for on-the-go study. --
Foundations of Nursing Practice. Factors influencing client needs and nursing care -- Basics of nursing practice -- Integral aspects of nursing care -- Foundations of nursing practice review questions with answers and rationales -- Medical-Surgical Nursing. Growth and development of the adult -- Nursing care of clients with circulatory system (cardiovascular, blood, and lymphatic systems) disorders -- Nursing care of clients with respiratory system disorders -- Nursing care of clients with gastrointestinal system disorders -- Nursing care of clients with endocrine system disorders -- Nursing care of clients with integumentary system disorders -- Nursing care of clients with neuromusculoskeletal system disorders -- Nursing care of clients with urinary/reproductive system disorders -- Nursing care of clients with infectious diseases -- Medical-surgical nursing review questions with answers and rationales -- Mental Health/Psychiatric Nursing. Foundations of mental health/psychiatric nursing -- The practice of mental health/psychiatric nursing -- Nursing care of clients with disorders usually first evident in infancy, childhood, or adolescence -- Nursing care of clients with disorders related to alternations in cognition and perception -- Nursing care of clients with disorders related to anxiety and alterations in mood -- Nursing care of clients with disorders related to alterations in behavior -- Nursing care of clients with sexual and gender identity disorders -- Mental health/psychiatric nursing review questions with answers and rationales -- Childbearing and Women's Health Nursing. Nursing care to promote childbearing and women's health -- Nursing care related to major disorders affecting women's health -- Nursing care of women during uncomplicated pregnancy, labor, childbirth, and the postpartum period -- Nursing care of women at risk during pregnancy, labor, childbirth, and the postpartum period -- Nursing care of the newborn -- Childbearing and women's health nursing review questions with answers and rationales -- Child Health Nursing. Foundations of child health nursing -- Nursing care of infants -- Nursing care of toddlers -- Nursing care of preschoolers -- Nursing care of school-age children -- Nursing care of adolescents -- Child health nursing review questions with answers and rationales -- NCLEX Preparation Toolkit. Comprehensive examination -- Study worksheets for reviewing your test-taking performance.
Includes index.
Keywords: NATIONAL COUNCIL LICENSURE EXAMINATION FOR REGISTERED NURSES -- STUDY GUIDES